2023
DOI: 10.1007/s12975-023-01202-z
|View full text |Cite
|
Sign up to set email alerts
|

Theta Frequency Electromagnetic Stimulation Enhances Functional Recovery After Stroke

Naohiko Okabe,
Mary Hovanesyan,
Srbui Azarapetian
et al.

Abstract: Extremely low-frequency, low-intensity electromagnetic field (ELF-EMF) therapy is a non-invasive brain stimulation method that can modulate neuroprotection and neuroplasticity. ELF-EMF was recently shown to enhance recovery in human stroke in a small pilot clinical trial (NCT04039178). ELF-EMFs encompass a wide range of frequencies, typically ranging from 1 to 100 Hz, and their effects can vary depending on the specific frequency employed. However, whether and to what extent the effectiveness of ELF-EMFs depen… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 65 publications
0
1
0
Order By: Relevance
“…While the study by Ma et al presents findings that differ from ours, this discrepancy could be attributed to their specific application of ELF-EMFs-a singular strength of 2 mT, 50 Hz for a duration of 3 days. A multitude of studies have indeed demonstrated that the effects observed post-ELF-EMF application are contingent on various parameters such as the frequency, strength, and duration of treatment [18,20]. Given this variability, it is not surprising to encounter contradictory effects.…”
Section: Pulsating Elf-emf Exposure and Potential For Nsc Differentia...mentioning
confidence: 99%
“…While the study by Ma et al presents findings that differ from ours, this discrepancy could be attributed to their specific application of ELF-EMFs-a singular strength of 2 mT, 50 Hz for a duration of 3 days. A multitude of studies have indeed demonstrated that the effects observed post-ELF-EMF application are contingent on various parameters such as the frequency, strength, and duration of treatment [18,20]. Given this variability, it is not surprising to encounter contradictory effects.…”
Section: Pulsating Elf-emf Exposure and Potential For Nsc Differentia...mentioning
confidence: 99%